1999
DOI: 10.1074/jbc.274.15.9937
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of the Small Heat Shock Protein IbpB from Escherichia coli

Abstract: Escherichia coli IbpB was overexpressed in a strain carrying a deletion in the chromosomal ibp operon and purified by refolding. Under our experimental conditions, IbpB exhibited pronounced size heterogeneity. Basic oligomers, roughly spherical and approximately 15 nm in diameter, interacted to form larger particles in the 100 -200-nm range, which themselves associated to yield loose aggregates of micrometer size. IbpB suppressed the thermal aggregation of model proteins in a concentration-dependent manner, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
107
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(116 citation statements)
references
References 64 publications
9
107
0
Order By: Relevance
“…The IbpA/B proteins associate with aggregated proteins (Allen et al, 1992;Laskowska et al, 1996b) and protect them from irreversible denaturation and extensive proteolysis. In other words, the IbpA/B proteins preserve denaturating proteins as a pool of substrates competent for refolding and reactivation by the ATP-dependent chaperone systems (Veinger et al, 1998;Shearstone & Baneyx, 1999;Kuczyń ska-Wiśnik et al, 2002;Kitagawa et al, 2002). This fits in with our observations.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The IbpA/B proteins associate with aggregated proteins (Allen et al, 1992;Laskowska et al, 1996b) and protect them from irreversible denaturation and extensive proteolysis. In other words, the IbpA/B proteins preserve denaturating proteins as a pool of substrates competent for refolding and reactivation by the ATP-dependent chaperone systems (Veinger et al, 1998;Shearstone & Baneyx, 1999;Kuczyń ska-Wiśnik et al, 2002;Kitagawa et al, 2002). This fits in with our observations.…”
Section: Discussionsupporting
confidence: 81%
“…The GrpE protein mediates transfer of a substrate protein from the DnaK system to GroEL/GroES (Bukau & Horwich, 1998). The DnaK system may also cooperate with ClpB93/ClpB79, HtpG Mogk et al, 1999;Thomas & Baneyx, 2000;Schlieker et al, 2002), the small heat-shock proteins IbpA/IbpB (Thomas & Baneyx, 1998;Veinger et al, 1998;Shearstone & Baneyx, 1999) or trigger factor, a peptidyl-prolyl isomerase having a chaperone activity (Hesterkamp et al, 1996;Teter et al, 1999). A possible role for GrpE in the interaction of the DnaK/DnaJ and ClpB systems emerges from the experiments of Zolkiewski (1999) on suppression of luciferase aggregation in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Purified IbpB forms 2-to 3-MDa oligomers, which, upon exposure to high temperature, dissociate into smaller ϳ600-kDa structures (39,40). The importance of these structural changes is not well understood.…”
mentioning
confidence: 99%
“…The importance of these structural changes is not well understood. IbpB protein was shown in vitro to suppress thermal aggregation of model substrate proteins in a concentrationdependent manner (39). Moreover, IbpB was also tested for the ability to cooperate with chaperones from the Hsp70 and Hsp100 families in substrate disaggregation and refolding (16,18).…”
mentioning
confidence: 99%
“…It is generally accepted that hydrophobic regions in LMM HSPs are important for substrate binding (Arrigo and Landry, 1994). Recently, the substrate-binding sites of pea HSP18.1 (Lee et al, 1997), ␣-crystallin (Sharma et al, 1998), and E. coli IbpB (Shearstone and Baneyx, 1999) have been identified and are located within the N-terminal half of the conserved ␣-crystallin domain, which is the equivalent region of Oshsp16.9 consensus II domain. Our previous studies on two Oshsp16.9 variants have shown that E. coli cells (pGST-N78 cells) producing N-terminal 78 amino acids of Oshsp16.9 (includes the consensus II region of plant LMM HSPs) can survive at high temperature, whereas E. coli cells (pGST-C108 cells) producing C-terminal 108 amino acids of Oshsp16.9 (includes both consensus I and II regions of plant LMM HSPs) cannot mitigate the detrimental effects of high temperature (Yeh et al, 1997).…”
Section: Discussionmentioning
confidence: 99%